The Extract of Merremia mammosa Tubers Increases the Cytotoxicity of Doxorubicin and Induces Apoptosis in 4T1 Malignant Cancer Cells - Aulia Nur Septiani; Fatiha Citra Effendi; Nadya Rianasari; Muhammad Yusuf Alfaqih; Afifah Nisa Al Qisthy; Edy Meiyanto; Muthi Ikawati (Indonesian Society for Cancer Chemoprevention, 2025)
Doxorubicin has been incorporated in cancer therapy regimes for wide-range malignancies, but it causes many side effects. These adverse effects can be overcome by combining doxorubicin with other ingredients that possess anticancer potential but are safe on normal cells. The tubers of Merremia mammosa, locally known as “Bidara Upas” in Indonesia, have been proven to have anticancer potential with resin glycosides as the active compounds. This research aims to develop the extract of M. mammosa’s tubers (MTE) as a co-chemotherapy agent for doxorubicin. A malignant cancer cell line, 4T1, was used as the model. MTE was obtained by maceration in 96% ethanol. The thin layer chromatography confirmed that MTE contains glycoside compounds. Administration of MTE to 4T1 cells showed cytotoxic activity with an IC50 value of 61 μg/mL as evaluated by MTT assay. The combination of MTE and doxorubicin exhibited synergistic cytotoxic effects with a combination index of <0.7. Moreover, MTE at around IC50 was able to cause DNA fragmentation indicating apoptosis as observed by the agarose gel electrophoresis.These data support our hypothesis that MTE may serve as a potential co-chemotherapeutic agent for doxorubicin; however, the apoptosis-inducing potency of the combination requires further investigation.Keywords: 4T1 cell, apoptosis, Bidara Upas, co-chemotherapy.